Modeled Impacts of Farming Practices and Structural Agricultural Changes on Nitrogen Fluxes in the Netherlands - Wim de Vries; Hans Kros; Oene Oenema (The Scientific World Journal)
In the Netherlands, nutrient emissions from intensive animal husbandry have contributed to decreased species diversity in (semi) natural terrestrial and aquatic ecosystems, pollution of groundwater, and possibly global warming due to N2O emissions. This paper presents the results of a modelling study presenting the impacts of both structural measures and improved farming practices on major nitrogen (N) fluxes, including NH3 and N2O emission, uptake, leaching, and runoff, in the Netherlands, using input data for the year 2000. Average annual fluxes (Gg N year–1) for the year 2000 were estimated at 132 for NH3 emission (160 Gg NH3 year–1), 28 for N2O emission, 50 for N inflow to groundwater, and 15 for N inflow to surface water at a total N input of 1046. At this input, nitrate (NO3) concentrations in groundwater often exceeded the target of 50 mg NO3 l–1, specifically in well-drained sandy soils. The ammonia (NH3) emissions exceeded emission targets that were set to protect the biodiversity of nonagricultural land. Improved farming practices were calculated to lead to a significant reduction in NH3 emissions to the atmosphere and N leaching and runoff to groundwater and surface water, but these improvements were not enough to reach all the targets set for those fluxes. Only strong structural measures clearly improved the situation. The NH3 emission target of 30 Gg NH3 year–1, suggested for the year 2030, could not be attained, however, unless pig and poultry farming is completely banned in the Netherlands and all cattle stay almost permanently in low emission stables.